The PSA testing dilemma: GPs' reports of consultations with asymptomatic men: a qualitative study - Clements, A; Watson, E; Rai, T; Bukach, C; Shine, B; Austoker, J (BioMed Central, 2007)
Background: The National Health Service Prostate Cancer Risk Management Programme (PCRMP) has recommended that screening for prostate cancer is available for asymptomatic men, on the understanding that they have been provided with full and balanced information about the advantages and limitations of the prostate-specific antigen (PSA) test. Guidance has been distributed to all GPs in England and Wales to assist in the provision of information to men. This study aimed to elicit GPs' accounts of their discussions with asymptomatic men who consult with concerns about prostate cancer in order to identify the degree to which the PCRMP guidance was reflected in these consultations. Methods: Qualitative interview study. Semi-structured telephone interviews with 21 GPs from 18 GP practices in Oxfordshire. Results: All GPs reported undertaking some discussion with asymptomatic men about the PSA test. They described focussing most of the discussion on the false-positive and false-negative rates of the test, and the risks associated with a prostate biopsy. They reported less discussion of the potential for diagnosing indolent cancers, the dilemmas regarding treatment options for localised prostate cancer and the potential benefits of testing. Considerable variation existed between GPs in their accounts of the degree of detail given, and GP's presentation of information appeared to be affected by their personal views of the PSA test. Conclusion: The GPs in this study appear to recognise the importance of discussions regarding PSA testing; however, a full and balanced picture of the associated advantages and limitations does not seem to be consistently conveyed. Factors specific to PSA testing which appeared to have an impact on the GPs' discussions were the GP's personal opinions of the PSA test, and the need to counter men's primarily positive views of the benefits of PSA testing. Awareness of the impact of their views on the consultations may help GPs give men a more balanced presentation of the benefits and limitations of the PSA test.